Literature Review: Gambaran Pengetahuan, Kepatuhan, Teknik Cuci Tangan dan Kejadian Infeksi Nosokomial - Dinda Rizki Dwi Maharani; Sih Ageng Lumadi; Diana Noor Fatmawati (PROFESSIONAL HEALTH JOURNAL, 2023)
Knowledge is the result of remembring information after someone researched a particular object such as hand washing techniques and the incidence of nosocomial infections. This study aims to determine overview of knowledge, compliance, hand washing techniques and the incidence of nosocomial infections.The method applied in this study is a literature review by applying the PICOS framework. The search results show that there were 14 journals that state that there was a description of knowledge, compliance, hand washing techniques and the incidence of nosocomial infections taken from three article search applications, used are Science direct, ProQuest and Google Scholar which were published from 2018-2020. Therefore, it can be concluded that adherence to hand washing techniques is needed in preventing the incidence of nosocomial infections, and the important role of health workers is needed to increase knowledge and health promotion about preventing and controlling the spread of infection.